Moderatism Paradigm of COVID-19 Prevention: Religion-Science Integration Perspective - Abd Hannan; Zainuddin Syarif (Dialogia, 2021)
One of phenomena in the handle of Covid pandemic is the polarization of religionists and scientists. This polarization occurs because the difference of paradigms from them in understanding about COVID-19. The religionists, who leans towards orthodoxy and conservatism, emphasize literal dogmatic approach, whereas the scientists emphasize on scientific approach with the principle of positivistic-materialism. This study discusses the paradigm of moderatism in COVID-19 prevention from integration of science and religion perspective. By using qualitive research and in-depth analysis based on John F. Haugt’s integration theory, this study found the idea of integration between science and religion as a paradigm of moderatism in COVID-19 prevention. This is an epistemological effort in order to create dialogical relationship between science and religion. It means that both fulfill and reinforce each other thereby augmenting the agenda of COVID-19 prevention. There is a need for epistemological transformation that both sides need to undergo to achieve the agenda. Religion, which has been embodied by a literal dogmatic perspective, needs to display dynamic and contextual. So, it can compromise with the reality especially in scientific approach. In the other hands, science which has followed positivistic-materialism principles. It should not be conducted free from all values but it should contain many values, especially spiritual and theistic. In contemporary religious discourse, the integration of science and religion in the context of COVID-19 prevention is a form of moderatism in responding the COVID-19 pandemic situation in terms of thinking, attitude, or behavior.